Infection, atherothrombosis and thromboembolism beyond the COVID-19 disease: what similar in physiopathology and researches - Correale, Michele (Aging Clin Exp Res, 2021)
The recent Sars-Cov-2 pandemic (COVID-19) has led to growing research on the relationship between thromboembolism and Sars-Cov-2 infection. Nowadays, endothelial dysfunction, platelet activation, coagulation, and inflammatory host immune response are the subject of extensive researches in patients with COVID-19 disease. However, studies on the link between microorganisms or infections and thrombotic or thromboembolic events met fluctuating interest in the past. We, therefore, aimed to briefly summarize previous evidence on this topic, highlighting common points between previous data and what experienced today with SARS-COV2 infections.